2021
DOI: 10.3390/diagnostics11030383
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Magnetic Resonance Cholangiopancreatography for Detecting Difficult Laparoscopic Cholecystectomy in Acute Cholecystitis

Abstract: Previous studies have shown that signal intensity variations in the gallbladder wall on magnetic resonance imaging (MRI) are associated with necrosis and fibrosis in the gallbladder of acute cholecystitis (AC). However, the association between MRI findings and operative outcomes remains unclear. We retrospectively identified 321 patients who underwent preoperative magnetic resonance cholangiopancreatography (MRCP) and early laparoscopic cholecystectomy (LC) for AC. Based on the gallbladder wall signal intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…8 Regional inflammation in acute cholecystitis is relatively common. [9][10][11][12][13][14][15] Prior reporting has suggested that in a non-negligible number of cases, regional inflammation may be a triggering factor for acute cholecystitis. 11…”
mentioning
confidence: 99%
“…8 Regional inflammation in acute cholecystitis is relatively common. [9][10][11][12][13][14][15] Prior reporting has suggested that in a non-negligible number of cases, regional inflammation may be a triggering factor for acute cholecystitis. 11…”
mentioning
confidence: 99%